Optimalisasi Kelas Ibu Hamil Sebagai Upaya Deteksi Dini Gangguan Neuromusculoskeletal Ibu Hamil: Optimizing Classes for Pregnant Women as an Effort for Early Detection of Neuromusculoskeletal Disorders in Pregnant Women - Lia Dwi Prafitri; Nina Zuhana; Dzikra Nurseptiani; Wahyu Ersila (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Indonesia's Maternal Mortality Rate (MMR) has yet to reach the SDGs goal by the end of 2030, which is less than 70% achievement targets. One of the reasons for the high MMR is the mother's inability to make decisions if there are problems during pregnancy. Providing knowledge to pregnant women and their families through pregnant women classes as an early detection effort to reduce MMR. Efforts for early detection are neuromusculoskeletal disorders of pregnant women. The purpose of this community service activity is to carry out early detection and increase the knowledge and skills of pregnant women about neuromusculoskeletal disorders in pregnant women. The method is carried out by conducting examinations for pregnant women, health education, and practical demonstrations on how to deal with neuromusculoskeletal disorders in pregnant women. The target of this activity is pregnant women who are in the working area of the Tirto Health Center, with as many as 51 pregnant women. The results of this community service activity are being able to carry out early detection of pregnant women by conducting health checks and increasing the knowledge of pregnant women about neuromusculoskeletal disorders with an average rating score of 23.06%. Pregnant women can practice how to deal with neuromusculoskeletal disorders in pregnant women. The Health Office can work with the Puskesmas and health workers, especially midwives, to carry out routine activities in conducting early detection of health problems in pregnant women through examinations, health counseling, or practice demonstrations on early detection of health in pregnant women.